Improving The Quality Of Graduates Of Early Children Education Study Program Through SPMI - Rifqi Zaeni Achmad Syam; R. Supyan Sauri; Rosiana Nurwa Indah (UHN IGB Sugriwa Denpasar, 2021)
This study aims to describe a strategy for improving the quality of graduates of the Early Childhood Education Study Program as an effort to improve the quality of education at the Nusantara Islamic University of Bandung. The research was conducted at the Early Childhood Education Study Program at Nusantara Islam University, with the subject of the Quality Assurance Unit (UPM) of the Early Childhood Education Study Program, Faculty of Teacher Training and Education. The method used in this study uses a qualitative approach with the case study method. Data collection techniques through direct observation, searching documents and archives, and in-depth interviews. The results showed that there were SPMI policies and concepts in the form of academic quality standard documents and non-academic quality standard documents compiled by the Quality Assurance Unit (UPM); Quality Assurance Unit (UPM) as the coordinator in the determination, implementation, evaluation, control and improvement of SPMI in the Early Childhood Education Study Program; SPMI implementation is carried out by drafting a design in the form of an SPMI cycle; The obstacles faced by leadership commitment are not optimal, the number of auditors is very limited, SPMI activities are only carried out as limited as routine steps taken in anticipation of obstacles in the form of providing experts in the implementation of SPMI, training for young auditors, fostering a spirit of quality assurance, conducting evaluations every semester. Utilization of the results of the SPMI evaluation in order to build a quality culture, BAN-PT accreditation and customer satisfaction.